MONITORING OF VIRAL INFECTION IN SWEET PEPPER PLANTS GROWN IN GREENHOUSE AND OPEN FIELD IN DIFFERENT CLIMATIC ZONES - M. I. Mamedov; O. N. Pishnaya; E. A. Dzhos; I. A. Engalycheva; E. A. Kozlovskaya (Овощи России, 2017)
35 viruses have been reported to infect peppers (Capsicum spp.) and those lead to economic losses like low  and  variable yield. Viral diseases are an important factor  provoking  low  yield and reduced  fruit  quality. In low volume hydroponics the spread of virus infection had local character. The two types of symptoms were revealed. The plants with symptoms of green mottle, chlorosis, deformation of mid-rib  in top leaves, and leaf blade rolling by edges inwardly were observed in breeding accessions with light-green fruit color such as ‘Maria’, ‘L-Ochrovanie’,  ‘Belosnezhka’. The deformation,  mottle and symptoms of inner necrosis can be seen on fruits. The degree of disease development reached 100%. The results of  enzyme-linked immunosorbent  assay (ELISA) and ImmunoStrips assays enabled to identify the tobacco mosaic  virus  (TMV). There  were  blight-yellow   mottle, wrinkling on entire plants and deformation and mottling on fruits. The symptoms appeared on the top leaves by the end of vegetation period that was caused by late viral impact. The degree of developing the disease was 10.5-25% on leaves and fruits that was less than on plants with green mosaic. Immunological  tests carried out  in open field showed the combined virus infections, consisting of TMV+CMV  with  degree  of  disease  development  was 37.5%. The rod-shaped particles, 30 nm in size, belonging to tobacco mosaic virus were discovered with the use of electron microscopy in pepper plants showing the symptoms of green and yellow mosaic.